Evaluación de la resistencia a la flexión y compresión de un concreto estructural ecológico con fibras pet propuesto conforme a la norma NSR-10 (2020)
In this research, the feasibility of using polyethylene terephthalate (PET) from plastic containers as an addition of fibers in concrete mixtures in construction projects was studied, in order to contribute to the environment without reducing the quality of constructions. The analysis was based on the elaboration of a mix design for a conventional concrete under the ACI 211.1 standard and the Fuller method, to which both commercial fibers from the Toxement brand and recycled fibres from PET plastic containers were added, and then subjected to compression and bending tests at curing ages of 4, 7 and 28 days. The specimens were tested in the laboratories of Universidad de la Costa and the company Consultch S.A.S. Based on the results obtained, the main statistical indicators were calculated for the respective analysis. The results obtained show that the concretes with 0.2% by volume of PET fibers presented a reduction of 9.89% in the compressive strength with respect to the control concrete, but when the percentage of PET fibers increased to 0.35 %, the reduction in compressive strength decreases to only 6.5% compared to control concrete. However, it was possible to maintain the flexural strength since the fibers improve the ductility and toughness of the concrete, so its use is recommended to control plastic shrinkage cracking.